Liraglutide restores chronic ER stress, autophagy impairments and apoptotic signalling in SH-SY5Y cells. Issue 1 (December 2017) - Panagaki, Theodora; Michael, Maria; Hölscher, Christian
Abstract Growing evidence suggests that agonists of glucagon-like peptide (GLP-1) receptor exert neuroprotective and neurorestorative effects across a range of experimental models of neuronal degeneration, and, recently, a pilot clinical trial of Liraglutide in Alzheimer's disease patients showed improvements in cerebral glucose consumption that signifies disease progression. However, the exact underlying mechanism of action remains unclear. Chronic endoplasmic reticulum (ER) stress has recently emerged as a mechanism for neuronal injury, rendering it a potent therapeutic target for acute and chronic neurodegenerative disorders. Here, we investigate the neuroprotective effects of Liraglutide along with the signalling network against prolong ER stress and autophagy impairments induced by the non-competitive inhibitor of sarco/ER Ca2+ -ATPase, thapsigargin. We show that Liraglutide modulates the ER stress response and elicits ER proteostasis and autophagy machinery homeostasis in human SH-SY5Y neuroblastoma cell line. These effects correlate with resolution of hyper-activity of the antioxidant Nrf2 factor and restoration of the impaired cell viability and proliferation. Mechanistically, Liraglutide engages Akt and signal transducer and activator of transcription 3 (STAT3) signalling to favour adaptive responses and shift cell fate from apoptosis to survival under chronic stress conditions in SH-SY5Y cells.